1977
DOI: 10.1007/bf02533627
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fats on the plasma lipid composition of sheep

Abstract: This study reports on the plasma lipid compositions of sheep fed either a control diet (C), a control diet supplemented with tallow (A) or polyunsaturated fatty acid (B) that had been protected against hydrolysis and hydrogenation in the rumen, or a control diet supplemented with maize oil (D). Diet B considerably increased the 18∶2 content of all the major plasma lipid fractions. Although the feeding of diet D also resulted in an increase in the 18∶2 contents within the cholesteryl ester, unesterified fatty a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In non-ruminant animals, where most of the dietary fat is absorbed as a mixture of 2-monoglyceride and free fatty acid, resynthesis of triglycérides via the monoglyceride pathway is known to predominate with the a-glycerophosphate pathway playing only a minor role although changes in intracellular substrate concentrations can sometimes alter the relative importance of the two pathways considerably. It could, for example, be important in mucosal triglycéride biosynthesis under certain specific dietary regimes such as in the feeding of fats protected against hydrolysis in the rumen by casein-formaldehyde treatment 218 (see Christie 44b ). In circumstances where there is an apparent excess of monoglyceride, some hydrolysis by a specific monoglyceride lipase within the mucosal cells may occur in order to provide sufficient free fatty acid for esterification of the remaining monoglyceride.…”
Section: B Resynthesis Of Lipid In the Intestinal Mucosal Cellsmentioning
confidence: 99%
“…In non-ruminant animals, where most of the dietary fat is absorbed as a mixture of 2-monoglyceride and free fatty acid, resynthesis of triglycérides via the monoglyceride pathway is known to predominate with the a-glycerophosphate pathway playing only a minor role although changes in intracellular substrate concentrations can sometimes alter the relative importance of the two pathways considerably. It could, for example, be important in mucosal triglycéride biosynthesis under certain specific dietary regimes such as in the feeding of fats protected against hydrolysis in the rumen by casein-formaldehyde treatment 218 (see Christie 44b ). In circumstances where there is an apparent excess of monoglyceride, some hydrolysis by a specific monoglyceride lipase within the mucosal cells may occur in order to provide sufficient free fatty acid for esterification of the remaining monoglyceride.…”
Section: B Resynthesis Of Lipid In the Intestinal Mucosal Cellsmentioning
confidence: 99%
“…One group received a daily diet of 500 g of good hay and 300 g of a cereal concentrate with water available ad libitum and was designated the control group. The second group received an identical diet except that, during the last 8 weeks of pregnancy, the concentrate ration was increasingly replaced by a 'protected' polyunsaturated oil supplement (14), the analysis of which is shown in table I.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…In spite of the lack of linoleic acid, a high concentration of archidonic acid was found in the fetal plasma. The association of this with the phospholipids of the HDL fraction in particular, in both the maternal and fetal plasmas, conforms to a pattern that has been described for a variety of animal species [4,25]. Although the distribution of fatty acids of the fetal lipoproteins results from both endogenous and exogenous sources [38], the influence of the placenta on fetal lipid supply and therefore on the composition and distri bution of the lipoproteins is indicated by a comparison with some recently obtained data on aspects of fatty acid metabolism within the ovine placenta.…”
Section: Discussionmentioning
confidence: 91%
“…The plasma fatty acid composition of the lipid components of the fetal plasma does in fact resemble that of simple-stomached animals in a state of essential fatty acid defi ciency [33], In several species it has been observed that large changes in the polyunsat urated fatty acid content of the plasma has been accompanied by a re-distribution of the major lipoprotein fractions, together with concomitant changes in the physical proper ties of the VLDL fraction [4,9,10,34], The possibility exists therefore that the differ ences in the distribution and composition of the lipoproteins between the mother and fe tus observed presently may have similar ori gins. However, it has also been shown in sim ple-stomached species [31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation